Impact of Infections in Patients with Acute Myeloid Leukemia Receiving Cytarabine+ Daunorubicin (7+3) Versus Azacitidine and Venetoclax during Induction Chemotherapy - Alam , Junaid; Panezai , Shakila Aziz; Shaikh , Usman; Kumari , Lavita; Muhammad Ilyas; kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Acute myeloid leukemia (AML) remains a challenging hematologic malignancy, with infections, treatment-related toxicity, and multidrug-resistant (MDR) organisms significantly contributing to high mortality, particularly in resource-limited settings. This study examined infection patterns, MDR prevalence, and induction outcomes in AML patients receiving standard regimens, including Cytarabine-anthracycline (7+3) and azacitidine-venetoclax (Aza/Ven), at a tertiary hospital in Pakistan. In this observational study, 176 AML patients aged ≥18 years treated from January 2018 to December 2023 were analyzed. Patients on the 7+3 (65.3%) and Aza/Ven (34.7%) regimens were assessed for demographics, clinical status, infection rates, organism profiles, antibiotic resistance, and survival outcomes using Kaplan‒Meier and Cox regression models. Patients on the 7+3 regimen experienced significantly higher neutropenia and infection rates (p<0.001). Among 106 isolates from blood cultures, 12.5% were MDR, with 63% being carbapenem-resistant Enterobacteriaceae (CRE). The Aza/Ven group exhibited a higher induction-related mortality rate (31.1%) compared to 7+3 (21.7%, p=0.03). Adjusted analysis revealed a six-fold increased risk of death with the Aza/Ven regimen (p<0.001). This study highlights the significant burden of infections and MDR organisms in AML patients, particularly those on Aza/Ven, often reserved for older or high-risk patients. The findings underscore the need for robust infection prevention, stringent antibiotic stewardship, and tailored treatments to optimize outcomes. Further research is essential to refine induction regimens that balance efficacy with infection-related risks, especially in resource-limited settings.